Guilt Aversion and Reciprocity in the Performance-Enhancing Drug Game. (May 2019) - Cartwright, Edward
We revisit the performance-enhancing drug game by applying models of guilt aversion and reciprocity. Both models fit within the framework of psychological game theory in that they allow payoffs to depend on beliefs. We explore the extent to which social norms can help reduce or eliminate doping in sport. With reciprocity, we see that first-order beliefs on the prevalence of doping are key and a norm of clean sport would require a coordinated shift in such beliefs. With guilt aversion, by contrast, second-order beliefs are key and individuals may have an incentive to race clean even if they expect competitors will dope. Our results point to the importance for sports bodies and coaches to manage the beliefs of athletes.